Diagnostic Accuracy of Doppler Ultrasonography in the Antenatal Diagnosis of Abnormal Placental Invasion Secondary to Placenta Praevia - Huda Sajid; Syed Mubarak Ali; Roomi Mahmud; Asma Javed; Ameet Jesrani (KARACHI MEDICAL AND DENTAL COLLEGE, 2018)
Objective: To  determine the diagnostic accuracy of Doppler Ultrasonography in a tertiary care hospital, for the antenatal diagnosis of abnormal placental invasion secondary to placenta praevia, taking operative findings of caesarean section as gold standard. Methods: This is a cross-sectional study carried out in the Department of Radiology, Liaquat National Hospital, Karachi, from 1st August 2013 to 31st July 2014. A total of 591  pregnant  women  (multipara) having placenta praevia were  included  in  this  study.  The  diagnosis  of  abnormal  placental  invasion  was made by Doppler USG and compared with operative findings of caesarean section as gold standard. A predesigned pro forma was used to document findings. SPSS version 17 was used for all sta-  tistical analysis. Results: Sensitivity, specificity, positive and negative predictive value as well as accuracy of Doppler ultrasonography (USG) in the detection  of  abnormal  placental  invasion  was  found  to  be  84.8%,  93.9%, 91.8%, 88.5% and 89.95%, respectively. Conclusion:  Any persistent placenta praevia, will benefit from antenatal Doppler USG studies to identify abnormal utero-placental vascular flow patterns and these findings clearly aid in the management of this most challenging obstetric complication.